Mapping Islamic Investment Literature and Its Implications for Public Sector Investment Policy in Indonesia: A Bibliometric Analysis - Ihza Manila, Hanifia; Gibreel Musa Saleh, Husny; Latipa Mangindalat, Rosda; Evayanti Redina, Wien; Setiawan, Yudi (Pusat Pengembangan Sumber Daya Manusia Aparatur, 2025)
Purpose– This study aims to map the development trends and thematic patterns in Islamic investment literature and explore their potential implications for public sector investment policies in Indonesia. As the government increases its commitment to Islamic financial instruments—such as sukuk, waqf-linked investment, and halal project financing—this study offers evidence to align research trends with national policy priorities.Design/methods/approach– The study employs a bibliometric analysis using the Scopus database, focusing on Islamic investment-related publications from 2013 to 2023. Tools such as VOSviewer and Biblioshiny (R Studio) were used to visualize keyword co-occurrence, authorship networks, thematic evolution, and journal relevance.Findings– The bibliometric analysis identified a growing number of publications in the last five years, with dominant themes including sukuk issuance, Islamic portfolio optimization, halal investment behavior, and Sharia compliance. Most studies remain concentrated in academic-financial discourse, with limited connection to policy implementation or public governance perspectives. Few studies address Islamic investment within public sector contexts, especially in Southeast Asia.Research implications/limitations– While this study presents comprehensive mapping, it does not evaluate the quality or impact of policy outcomes associated with Islamic investment initiatives. Future studies are encouraged to connect bibliometric insights with public budgeting, Islamic infrastructure development, and fiscal planning in Muslim-majority countries.Originality/value– This research contributes by linking academic literature on Islamic investment with the broader agenda of public sector innovation and financial policy development. It highlights the need for inclusive and Sharia-based financial strategies in public administration and invites policymakers to engage with academic insights for better governance outcomes.